Pengaruh Keberadaan Financial Technology (Fintech) dan Jumlah Pembiayaan Pada Ukuran Perusahaan - Gine Das Prena; Wangi Fitriani (STATERA: Jurnal Akuntansi dan Keuangan, 2020)
The development of science and technology is increasingly rapid in the digital era today has influenced the pattern of human behavior in accessing various information and various features of electronic services. FINTECH (Financial Technology) is a liaison technology between the financial sector and users or the general public and in this study will discuss how the existence of Fintech (Financial Technology), and the amount of financing affect the Size of the Company. Data thati used in this study is quantitative datai research and the secondhary data are the sources od this research datai. Data collection techniques in this study used documentation techniques and data analysis techniquest using normality tests and classic assumption tests and using multiple linear regression analysis instruments using SPSS 22 application assistance.